Comparison of the effect of two different doses of recombinant gonadotropin for ovarian stimulation on the outcome of intrauterine insemination - Ming-Ting Chung; Te-Fu Chan; Tao-Chuan Loo; Hsun-Han Tang; Liang-Yin Lin; Yung-Chieh Tsai (Elsevier, 2011)
Objective: The aim of this study was to identify an optimal stimulation protocol for intrauterine insemination (IUI) to obtain an acceptable pregnancy rate and low frequency of multiple pregnancies. Materials and Methods: In total, 340 patients, who received intrauterine insemination because of ovulation dysfunction, were enrolled in this study. Group I consisted of 203 patients who received recombinant FSH (r-FSH) 150 U every other day as an ovulation induction agent. Group II consisted of 137 patients who received r-FSH 100 U every other day as an ovulation induction agent. All patients in both groups also received clomiphene citrate 100 mg/day for consecutive five days from the fifth day of the cycle. Only patients with at least two follicles >18 mm on the human chorionic gonadotropin injection days were included in this study. Results: The clinical pregnancy rate was 14.8% (30/203) in Group I compared with 20.4% (28/137) in Group II, p > 0.05. The incidence of multiple pregnancy was 41.7% (10/24) in Group I compared with 12.5% (3/24) in Group II, p < 0.05. Conclusions: The concurrent use of low-dose r-FSH and clomiphene citrate would seem not only to be cost-effective but also highly satisfactory in that it prevents high-order multiple pregnancies.